2016
DOI: 10.1038/ncomms12887
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylated parafibromin is a transcriptional coactivator of the Wnt/Hedgehog/Notch pathways

Abstract: Evolutionally conserved Wnt, Hedgehog (Hh) and Notch morphogen pathways play essential roles in the development, homeostasis and pathogenesis of multicellular organisms. Nevertheless, mechanisms that intracellularly coordinate these signal inputs remain poorly understood. Here we found that parafibromin, a component of the PAF complex, competitively interacts with β-catenin and Gli1, thereby potentiating transactivation of Wnt- and Hh-target genes in a mutually exclusive manner. Parafibromin also binds to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 55 publications
(92 reference statements)
2
48
0
Order By: Relevance
“…We identified another tumor with a mutation in CDC73 , which encodes the RNA polymerase II–associated factor complex protein parafibromin and was recently reported to potentiate Notch signaling by binding to the NICD. 36 We also found an EP300 mutation in the validation cohort that could abrogate signaling of the Notch transcriptional complex. Of note, Notch signaling was reported to have a tumor suppressor function in GIST by down-regulating KIT mRNA expression.…”
Section: Discussionmentioning
confidence: 62%
“…We identified another tumor with a mutation in CDC73 , which encodes the RNA polymerase II–associated factor complex protein parafibromin and was recently reported to potentiate Notch signaling by binding to the NICD. 36 We also found an EP300 mutation in the validation cohort that could abrogate signaling of the Notch transcriptional complex. Of note, Notch signaling was reported to have a tumor suppressor function in GIST by down-regulating KIT mRNA expression.…”
Section: Discussionmentioning
confidence: 62%
“…Further, HMGA1 expression has been found to be induced by transforming growth factor beta (TGF‐β) signalling through specificity protein 1 and phosphatidyl inositol‐3 kinase, resulting in enhanced tumourigenic properties in breast carcinoma . High Mobility Group AT‐hook 1 could arguably act downstream of the sonic hedgehog pathway to inactivate the tumour suppressor parafibromin (mutated hyperthyroidism jaw‐tumour 2) resulting in aberrant cell‐cycle progress . In breast carcinoma, HMGA1 is crucial to activation of several signalling pathways like Wnt, Notch, and Pin1‐dependent; TGF‐β/specificity protein 1/phosphatidyl inositol‐3 kinase; and Ras/extracellular signal‐regulated kinase (ERK) signalling pathways, which consequently boosts EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also identified an important role for parafibromin, the human ortholog of Cdc73, in regulating the transcriptional output of the developmentally critical Wnt, Hedgehog, and Notch signaling pathways through direct interactions with the downstream effectors of these pathways [33, 50]. The interactions between parafibromin and the effectors of the Wnt and Hedgehog pathways (β-catenin and Gli1, respectively) utilize the same N-terminal segment of parafibromin and are mutually exclusive [50].…”
Section: Mechanisms Of Targeting Paf1c To Chromatinmentioning
confidence: 99%
“…The interactions between parafibromin and the effectors of the Wnt and Hedgehog pathways (β-catenin and Gli1, respectively) utilize the same N-terminal segment of parafibromin and are mutually exclusive [50]. In contrast, parafibromin can simultaneously interact with the Wnt and Notch signaling effectors, allowing for coordinate stimulation of these two pathways.…”
Section: Mechanisms Of Targeting Paf1c To Chromatinmentioning
confidence: 99%